1976
DOI: 10.1159/000180738
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic Skeletal Changes in Uremic Patients on Regular Hemodialysis

Abstract: 99Tcm-polyphosphate (Tc-PP) bone scintigraphy was performed in 30 consecutive uremic patients on regular hemodialysis and compared with a normal control group. 27 of the patients (90%) had pathological accumulation on the scintigrams, while roentgenographic abnormalities were present in only 10 patients (33%), indicating that scintigraphy is superior to X-ray in the early detection of skeletal changes in uremic patients. In the group with the most pronounced uptake on the scintigrams ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Increased pulmonary uptake of the tracer was found in 11 of the 105 kidney-transplanted patients corresponding to the 10% demon strated in patients on chronic hemodialysis [15]. It has been suggested that this finding reflects pulmonary calcification [2,7,10,13,19,20], In the present investigation no patients showed radiographic evidence of calcification of the lungs.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…Increased pulmonary uptake of the tracer was found in 11 of the 105 kidney-transplanted patients corresponding to the 10% demon strated in patients on chronic hemodialysis [15]. It has been suggested that this finding reflects pulmonary calcification [2,7,10,13,19,20], In the present investigation no patients showed radiographic evidence of calcification of the lungs.…”
Section: Discussionsupporting
confidence: 49%
“…Il has further been suggested that the complexes are attached to the free aldehyde groups of the collagen molecule [3.22,23], Thus the Tc-PP scinti graphy in the evaluation of metabolic bone disease is not specific and should be supple mented with other investigations to secure the diagnosis of the bone lesion. Nevertheless, Tc-PP scintigraphy applied to metabolic bone disease has recently been shown to be of signi ficant importance [11,15,21,22], In a previous investigation [15] 90% of hemodialysis patients showed scintigraphic signs of generalized bone disease. In the pre sent investigation on kidney-transplanted pa tients only 49% had generalized scintigraphic changes, demonstrating that renal osteodys trophy is less frequent after a kidney trans plantation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations